The Influence of Content Marketing and Influencer Marketing on the Purchase Decision of Skintific Cushion on the Tiktok Application - Tanzalina Aulia Rahma; Zumrotul Fitriyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Technological developments encourage companies to utilize social media as a marketing tool, one of which is Skintific as a beauty brand that actively uses TikTok to promote its products. This study aims to analyze the influence of content marketing and influencer marketing on purchasing decisions for Skintific cushions on the TikTok application. The study applies a quantitative approach with a population of consumers who have purchased Skintific cushions on the TikTok application. Samples were taken using non-probability sampling with a purposive sampling technique by distributing questionnaires to 108 respondents. The data were analyzed using the Partial Least Square (PLS) method with SmartPLS, and it was found that content marketing and influencer marketing contributed to purchasing decisions.